Effect of integrated nutrient management on coconut (Cocos nucifera) based cropping systems in south Gujarat (Current Horticulture, 2024)
An experiment was conducted on 27-year-old coconut (Cocos nucifera L.) garden to evaluate the productivity of coconut- based cropping system involving banana (Musa sp.), elephant -foot yam (Amorphophallus paeoniifolius [Dennst] Nicolson), tannia (Xanthosoma sagittifolium L.) and turmeric (Curcuma longa L.) with three integrated nutrient management (INM) practices, viz., T1- 75% of recommended dose of fertilizers (RDF) + 25% of N through organic recycling with vermicompost, T2- 50% of RDF + 50% of N through organic recycling with vermicompost + vermiwash application + biofertilizer application + in situ green manuring (sunhemp), T3- fully organic: 100% N through organic recycling with vermicompost + vermiwash application + biofertilizer application + in situ green manuring (sunnhemp) and green leaf manuring + composted coir pith, husk incorporation, and mulching with coconut leaves were imposed in coconut-based cropping system. For comparison, T4- control: monocrop of coconut with recommended NPK was maintained. Four treatments were laid out in a block of 0.25 ha area each for five years (2015-16 to 2019-20). Results showed that yield under T2 (146 nuts/palm) and T3 (136 nuts/palm) were on par and differed significantly compared to monocrop (117 nuts/ palm). With respect to component crops yield, viz., banana (8.27 t/ha), elephant- foot yam (13.90 t /ha), tannia leaves (65,605) and turmeric rhizome yield (12.06 t/ha) were higher under T2 treatment. The maximum gross and net returns were recorded in T2 (` 6,08,285 and ` 4,35,167) with BC ratio of 2.50, followed by T1 (` 5,35,226 and ` 3,71,789) with BC ratio of 2.20.
Keywords: Coconut; Cropping system; Coastal; Productivity; Nut yield